Recycling & redesigning logos : a designer's guide to refreshing & rethinking design - Hodgson, Michael (Michael R.); Porter, Matthew (Beverly, Mass. : Rockport Publishers, 2010)
This title demonstrates the strategies and processes of successful redesigns and shows readers how to build on the equity the brand already retains to create a fresh look. The case studies feature before and afters of the logos and discuss why the redesign was necessary.
Keywords: Logos (Symbols) -- Design